2018
DOI: 10.1111/gcb.14091
|View full text |Cite
|
Sign up to set email alerts
|

Cover crops mitigate direct greenhouse gases balance but reduce drainage under climate change scenarios in temperate climate with dry summers

Abstract: Cover crops provide ecosystem services such as storing atmospheric carbon in soils after incorporation of their residues. Cover crops also influence soil water balance, which can be an issue in temperate climates with dry summers as for example in southern France and Europe. As a consequence, it is necessary to understand cover crops' long-term influence on greenhouse gases (GHG) and water balances to assess their potential to mitigate climate change in arable cropping systems. We used the previously calibrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 53 publications
3
39
1
Order By: Relevance
“…This second effect was more evident in scenarios that maintain legumes for a longer time due to higher N availability. These results are consistent with recent simulation studies by Tribouillois, Constantin, and Justes (2018) when applying the STICS soil-crop model to 12 cropping systems in five locations in France, and with Lugato, Bampa, Panagos, Montanarella, and Jones (2014) when conducting large-scale simulations with CENTURY in Europe. Similar results were reported from field experiments conducted under various environmental conditions (García-González, Hontoria, Gabriel, Alonso-Ayuso, & Quemada, 2018;Mazzoncini, Sapkota, Bàrberi, Antichi, & Risaliti, 2011;Quemada, Cabrera, & McCracken, 1997;Thomsen & Christensen, 2004) and summarized in two meta-analysis (Abdalla et al, 2019;Aguilera et al, 2013;Poeplau & Don, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…This second effect was more evident in scenarios that maintain legumes for a longer time due to higher N availability. These results are consistent with recent simulation studies by Tribouillois, Constantin, and Justes (2018) when applying the STICS soil-crop model to 12 cropping systems in five locations in France, and with Lugato, Bampa, Panagos, Montanarella, and Jones (2014) when conducting large-scale simulations with CENTURY in Europe. Similar results were reported from field experiments conducted under various environmental conditions (García-González, Hontoria, Gabriel, Alonso-Ayuso, & Quemada, 2018;Mazzoncini, Sapkota, Bàrberi, Antichi, & Risaliti, 2011;Quemada, Cabrera, & McCracken, 1997;Thomsen & Christensen, 2004) and summarized in two meta-analysis (Abdalla et al, 2019;Aguilera et al, 2013;Poeplau & Don, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, they found that the radiative cooling effects would be reinforced by a decrease/increase in the sensible/latent heat fluxes at the surface. In another study, Tribouillois et al (2018), showed that, compared to bare soil, cover crops increased evapotranspiration (i.e. latent heat fluxes) without limiting the water resources for the next crop, if the cover crop were buried one month before seeding.…”
Section: Discussionmentioning
confidence: 99%
“…by integrated soil fertility management) could help in reducing gas emissions (Guardia et al, 2016;Tribouillois et al, 2018). Previous studies reported contrasting results with regard to cover crop effects on direct N 2 O emissions (Abdalla et al, 2013;Basche et al, 2014;Mitchell, Castellano, Sawyer, & Pantoja, 2013 (Kim et al, 2015) by limiting N availability.…”
Section: Impacts Of Cover Crops (Legume Nonlegume and Legume-non-lmentioning
confidence: 99%
“…This is obviously because cover crops are rarely grown in dry climates as they use water that could be used to grow a primary crop and reduce water percolation by transpiration (Weinert, Pan, Moneymaker, Santo, & Stevens, 2002). Tribouillois et al (2018) and Wortman et al (2012) reported that the large quantity of soil water used by the cover crops, at the cost of the subsequent primary crop and immobilization of soil N due to incorporation of low quality cover crop residues into the soil, is also a major concern. Tribouillois et al (2018) and Wortman et al (2012) reported that the large quantity of soil water used by the cover crops, at the cost of the subsequent primary crop and immobilization of soil N due to incorporation of low quality cover crop residues into the soil, is also a major concern.…”
Section: Influences Of Management Soil and Climatic Zones On Covermentioning
confidence: 99%